Current AI applications by Estonian tax authorities and use case scenarios - Künnapas Kaido; Maslionkina Palina; Hinno Risto; Liberts Raivis (TalTech Journal of European Studies)
Artificial intelligence (AI) is revolutionizing tax compliance and fraud detection, offering tax authorities unprecedented opportunities to enhance their efficiency and accuracy. This article explores the AI-based tax technology tools designed and implemented by the Estonian Tax and Customs Board in its daily operations. It analyses three main applications of AI: language models to assist taxpayers in their searches, network models to uncover connections between entities and individuals, and X-ray imaging systems to identify the nature of goods in packages for customs purposes. These technologies aim to assist taxpayers in understanding their rights, while simultaneously preventing and detecting tax fraud. Beyond the technological aspects, this discussion addresses the contributions of these tools to the legal sphere and their compatibility with the proactive law approach.